Multiple locations of near-infrared coronal lines in NGC 5548. Issue 3 (2nd September 2022) - Kynoch, Daniel; Landt, Hermine; Dehghanian, Maryam; Ward, Martin J; Ferland, Gary J
ABSTRACT: We present the first intensive study of the variability of the near-infrared coronal lines in an active galactic nucleus (AGN). We use data from a 1-yr-long spectroscopic monitoring campaign with roughly weekly cadence on NGC 5548 to study the variability in both emission line fluxes and profile shapes. We find that in common with many AGN coronal lines, those studied here are both broader than the low-ionizaton forbidden lines and blueshifted relative to them, with a stratification that implies an origin in an outflow interior to the standard narrow line region. We observe for the first time [S viii ] and [Si vi ] coronal line profiles that exhibit broad wings in addition to narrow cores, features not seen in either [S ix ] or [Si x ]. These wings are highly variable, whereas the cores show negligible changes. The differences in both the profile shapes and variability properties of the different line components indicate that there are at least two coronal line regions in AGN. We associate the variable, broad wings with the base of an X-ray heated wind evaporated from the inner edge of the dusty torus. The coronal line cores may be formed at several locations interior to the narrow line region: either along this accelerating, clumpy wind or in the much more compact outflow identified with the obscurer and so emerging on scales similar to the outer accretion disc and broad-line region.